Blood pressure categorization and subclinical left ventricular dysfunction in antihypertensive medication‐naive subjects. (24th February 2022) - Nakanishi, Koki; Daimon, Masao; Yoshida, Yuriko; Ishiwata, Jumpei; Sawada, Naoko; Hirokawa, Megumi; Kaneko, Hidehiro; Nakao, Tomoko; Mizuno, Yoshiko; Morita, Hiroyuki; Di Tullio, Marco R.; Homma, Shunichi; et al.
Abstract: Aims: The impact of blood pressure (BP) levels on subclinical left ventricular (LV) dysfunction and possible sex‐specific difference remains unclarified. This study investigated the relationship between BP categories given in the new 2017 American College of Cardiology (ACC)/American Heart Association (AHA) guideline and subclinical LV dysfunction in subjects free of cardiac disease. Methods and results: We examined antihypertensive medication‐naive 858 individuals who underwent extensive cardiovascular health check‐up. LV global longitudinal (LVGLS) and circumferential strain (LVGCS) were assessed by two‐dimensional speckle‐tracking echocardiography. Participants were categorized into four groups: normal BP, elevated BP, isolated diastolic hypertension (IDH), and systolic hypertension (SH). Among the 858 participants, 422 individuals had normal BP, 113 had elevated BP, 160 had IDH, and 163 had SH. Prevalence of abnormal LVGLS (>−18.6%) was greatest in SH (19.0%), followed by IDH (17.5%), elevated BP (14.2%), and normal BP (7.1%, P  < 0.001); no significant differences were observed for LVGCS ( P  = 0.671). In the multivariable analyses, IDH and SH were associated with impaired LVGLS [adjusted odds ratio (OR) 2.69 and 2.66, P  < 0.001], and borderline significance was observed for elevated BP (adjusted OR 1.90, P  = 0.060); there was no significant association between any of the BP groups and LVGCS. In sex‐stratified analysis, IDH and SH carried the significant risk of abnormal LVGLS in both sexes, while elevated BP was associated with LVGLS only in women. Conclusions: Isolated diastolic hypertension and SH redefined by ACC/AHA guideline carried significant risk for LVGLS, but not LVGCS. Elevated BP was associated with LVGLS only in women. Our findings provide information on cardiac correlates of the newly established BP categories.